Effect of the support on physicochemical properties and catalytic performance of cobalt based nano-catalysts in Fischer-Tropsch reaction - Ali, S. (Elsevier Ltd, 2017)
In this paper, comparative investigations of the effects of CNTs and γ-Al2O3 on the physicochemical properties and catalytic performances of Co based nano-catalyst during FTS have been presented. Catalysts were prepared via a wet impregnation method and characterized by various analytical techniques such as transmission electron microscopy (TEM), temperature programmed reduction (H2-TPR), carbon dioxide temperature programmed desorption (CO2-TPD) and X-ray photoelectron spectroscopy (XPS). Fischer-Tropsch reaction (FTS) was carried out in a fixed-bed microreactor (220 °C and 1 atm and with H2/CO = 2 v/v, SV of 12 L/g h). Various characterization techniques revealed that Co nanocatalysts supported on CNTs and Al2O3 were different in physicochemical properties. There was a stronger interaction between Co and Al2O3 support compared to that of CNTs support. CNTs support increased the reducibility, dispersion, active metal surface area and decreased Co particle size. A significant increase in CO conversion and FTS reaction rate was also observed over CNTs support compared to that of Co/Al2O3. Co/CNTs resulted in higher C5+ hydrocarbons selectivity compared to that of Co/Al2O3 catalyst. © 2017 Elsevier Ltd